2004
DOI: 10.1162/089892904322755557
|View full text |Cite
|
Sign up to set email alerts
|

Posttraining Sleep Enhances Automaticity in Perceptual Discrimination

Abstract: Perceptual learning can develop over extended periods, with slow, at times sleep-dependent, improvement seen several days after training. As a result, performance can become more automatic, that is, less dependent on voluntary attention. This study investigates whether the brain correlates of this enhancement of automaticity are sleep-dependent. Event-related potentials produced in response to complex auditory stimuli were recorded while subjects' attention was focused elsewhere. We report here that following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
72
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 70 publications
9
72
0
Order By: Relevance
“…Contrary to any prediction, subjects tested with 24 hours of sleep deprivation performed as well as the control group. Similar results were seen in subjects trained in a sound discrimination task (Atienza et al 2004). In that study, both control and sleep deprived subjects showed increased accuracy and speed when tested 48 hours after completion of training, without intervening practice.…”
Section: Discussionsupporting
confidence: 77%
“…Contrary to any prediction, subjects tested with 24 hours of sleep deprivation performed as well as the control group. Similar results were seen in subjects trained in a sound discrimination task (Atienza et al 2004). In that study, both control and sleep deprived subjects showed increased accuracy and speed when tested 48 hours after completion of training, without intervening practice.…”
Section: Discussionsupporting
confidence: 77%
“…Evidence of sleep-dependent skill learning has now been demonstrated across a wide variety of skill domains, including the visual (Karni et al, 1994;Gais et al, 2000;Stickgold et al, 2000), auditory (Atienza et al, 2004;Gaab et al, 2004), and motor (Smith and MacNeill, 1994;Fischer et al, 2002;Walker et al, 2002Walker et al, , 2003Kuriyama et al, 2004) systems. Specifically, sleep has been implicated in the ongoing process of consolidation after initial acquisition, whereby delayed learning could occur in the absence of further practice (Smith, 1995;Stickgold et al, 2001;Walker and Stickgold, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In general, P3a and P3b responses are suitable for studying both bottomup and top-down influences; they are modulated by attention, subjective probability (familiarity), difficulty levels, and stimulus features such as the relative saliency when compared to frequent sounds. P3a and P3b responses show both short-and long-term plasticity changes following auditory training (Atienza, Cantero, & Stickgold, 2004;Uther, Kujala, Huotilainen, Shtyrov, & Näätänen, 2006). Within a single session, P3a and P3b amplitudes show repetition-dependent reductions for target sounds in the frontal areas and a shift from frontal to parietal cortical activation during both active and passive listening conditions (Friedman, Kazmerski, & Cycowicz, 1998).…”
mentioning
confidence: 98%